Atlantoaxial Fixation Techniques Commonly Used and New Techniques (Translational Medicine Research,, 2018)
This book introduces posterior atlantoaxial fixation techniques and their biomechanical stability and clinical outcomes. Based on the full review of established techniques, authors discusses their advantages and disadvantages. Furthermore, the author discusses how to use the basic theories of translational medicine to achieve the modification of the posterior atlantoaxial fixation. It also proposes the modification of integrative "screw and hooks" and "long screw tail". Readers can learn the basic techniques of posterior atlantoaxial fixation and the major requirements.